THE EFFECT OF COMPETENCE AND PUBLICATION QUALITY ON LECTURER PERFORMANCE WITHIN THE PEMALANG ISLAMIC RELIGIOUS INSTITUTE, CENTRAL JAVA - Chasan Ma'ruf; Muhammad Ramdhan; Ichsan Gaffar (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ, 2025)
Lecturer performance in the Tri Dharma is shaped by competencies, motivation, publications, facilities, and ethics, while research and community service still face significant challenges requiring continuous quality enhancement. This study aims to determine the influence of competence and publication quality, both partially and simultaneously, on the performance of lecturers at the Islamic Religious Institute of Pemalang in Central Java. The research method is quantitative through a correlational approach. Data was collected using a questionnaire (Likert scale), with data processing through validity and reliability tests, classical assumption tests, t-tests, and F-tests. The research shows that lecturer competence (t=0.797, sig.=0.430) and publication quality (t=1.405, sig.=0.167) do not significantly affect performance. Their R Square values (0.079 and 0.107) indicate minimal contributions. The simultaneous F-test (2.871, sig.=0.068) also confirms no significant combined effect, with a total R Square of only 0.057. This means 94.3% of lecturer performance is influenced by other factors beyond those examined in this model. To conclude, lecturer competence and publication quality do not significantly affect performance, with a small contribution, and are influenced by other external factors.